Feasibility of the use of Landsat imagery to map soybean crop areas in Paraná, Brazil - Sugawara, Luciana Miura; Rudorff, Bernardo Friedrich Theodor; Adami, Marcos (Pesquisa Agropecuaria Brasileira, 2009)
The aim of this work was to evaluate the feasibility of the use of Landsat imagery to map soybean crop areas in Paraná, Brazil, during crop years from 2000/2001 to 2006/2007. The analysis of the quick look images from the TM and ETM+ sensors was performed to select useful images to map soybean crop. The quick looks were classified according to the presence or absence of clouds and technical problems. It was verified that for none of the seven crop years it would have been possible to map soybean crop for the entire Paraná state, even for the three crop years during which both satellites Landsat 5 and 7 were operating simultaneously. The presence of clouds, detected through the optical sensors, should be considered for systematic mapping of summer crops in Brazil.